2008
DOI: 10.3139/217.2010
|View full text |Cite
|
Sign up to set email alerts
|

Non-Isothermal Simulation of the Film Blowing Process Using Multi-Mode Extended Pom-Pom Model

Abstract: Plastic films are largely produced using the film blowing process. Branched polymers such as LDPE are commonly used in this process to produce a variety of plastic films. In this study, recently developed eXtended Pom-Pom (XPP) model, which focuses on describing rheological behavior of branched polymers, is employed to analyze the non-isothermal flow in the film blowing process. Furthermore, the Nakamura equation for crystallization kinetics is employed to consider crystallization effects and improve predictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 23 publications
2
14
0
Order By: Relevance
“…For the above presented parameters, the Figures 7-9 were generated. In more detail, the Zatloukal-Vlcek model predictions for the bubble shape (Figure 7), velocity ( Figure 8) and temperature profiles ( Figure 9) are compared with Tas's experimental data [16] together with theoretical predictions by Beaulne and Mitsoulis model [13] and Sarafrazi and Sharif [14] model. Based on the Figures 7-9 and Table 7, it is nicely visible that the predictions of the Zatloukal-Vlcek model are in very good agreement with the experimental data.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the above presented parameters, the Figures 7-9 were generated. In more detail, the Zatloukal-Vlcek model predictions for the bubble shape (Figure 7), velocity ( Figure 8) and temperature profiles ( Figure 9) are compared with Tas's experimental data [16] together with theoretical predictions by Beaulne and Mitsoulis model [13] and Sarafrazi and Sharif [14] model. Based on the Figures 7-9 and Table 7, it is nicely visible that the predictions of the Zatloukal-Vlcek model are in very good agreement with the experimental data.…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of the bubble shape between the Zatloukal-Vlcek model prediction [28], experimental data for the LDPE L8 taken from Tas´s Ph.D. thesis [16] and (a) the Beaulne and Mitsoulis model prediction [13]; (b) the Sarafrazi and Sharif model prediction [14]. [28], experimental data for the LDPE L8 taken from Tas´s Ph.D. thesis [16] and (a) the Beaulne and Mitsoulis model prediction [13]; (b) the Sarafrazi and Sharif model prediction [14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This formulation became a basic idea for many researchers (see summarization provided in Muke et al [7]), such as Pearson and Gutteridge (1978) [8], Cao and Campbell (1990) [9], Liu et al (1995) [10], or in the last years e.g. Muslet and Kamal (2004) [11], Beaulne and Mitsoulis (2007) [12], Sarafrazi and Sharif (2008) [13]. It has been found that the challenging task in the complex film blowing modeling is low stability of the numerical schemes which limits utilization of such models for wide parametric study, which could allow deeper fundamental understanding of the film blowing process.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of a rapid growth of a blown film coextrusion in the last decades, the number of experimental and modeling studies for this process is very limited [5][6][7][8][9][10][11][12] as well as number of works focused on modeling of heat transfer in film blowing process [8,[13][14][15][16][17][18][19][20]. In order to extend the knowledge in this area, the main goal of this work is to investigate effect of the heat transfer coefficient on temperature profile along the bubble for multi-layer film blowing process by using variational principles.…”
Section: Introductionmentioning
confidence: 99%